ANALYSIS OF THE QUALITY OF SERVICE ON CUSTOMER SATISFACTION AND LOYALTY PT BANK RIAU KEPRI SYARIAH IN PEKANBARU - Lusi Tri Hadiningsih; Jushermi '; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study is to know the effect of the quality of service on customer satisfaction of PT Bank Riau Kepri Syariah Pekanbaru and to know the effect of customer satisfaction on customer loyalty of PT Bank Riau Kepri Syariah Pekanbaru. The population in this study were customers of Bank Riau Kepri Syariah Pekanbaru. The samples in this study were 100 people by using accidental technique sampling. Analysis of this research was path analysis method (Two Step Regression) by using SPSS Version 20. Based on testing results that has been done, the first track test result is quality of service has a significant effect on customer satisfaction. And the second track test result is customer satisfaction has a significant effect on customer loyalty.Keywords: Quality of service, Satisfaction and loyalty